Pengaruh Persentase Penambahan Bubuk Daun Stevia rebaudiana Bertoni dan Lama Penyeduhan terhadap Karakteristik Minuman Kunyit Asam - Julianto, Aman; Mulyani, Sri; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
The leaves of the Stevia rebaudiana Bertoni plant have glycoside compounds including stevioside and rebaudioside A which can be used as natural sweeteners to replace the artificial sweeteners such as aspartame. This sweetener has a sweetness level of 200-300 times that of sucrose, so it can be used as a non-calorie sweetener. One way to take advantage of these leaves is to brew directly on certain products. This study aims to determine the effect of the addition percentage and the duration of brewing stevia leaves on the characteristics of tamarind turmeric drink and determine the appropriate treatment to produce the best tamarind drink. This study used a randomized block design with two factors. The first factor is the percentage of addition of stevia leaves with 4 levels, namely 15, 20, 25 and 30%. The second factor is the length of brewing with 3 levels, namely 2, 3 and 4 minutes. The results showed that the treatment of the percentage of addition of stevia leaves had an effect on vitamin C levels and antioxidant activity of IC 50 . The treatment duration of brewing had an effect on the level of vitamin C, while the interaction between the percentage of addition and the duration of brewing had an effect on the ranking of sweetness and the preference for sour turmeric drink.. The addition of 15% stevia leaf powder by brewing for 2 minutes resulted in the best tamarind turmeric drink with the characteristics of IC 50 namely 15.78 + 0.38 mg/ml, vitamin C level specifically 14.02 + 1.15 mg AAE/g extracts and ph was 3.33 + 0.18 and the sweet and hedonic taste ratings are slightly sweet and slightly likable, respectively. Keywords : Brewing time, stevia addition, turmeric-tamarind drink